Perspektif Iman Remaja akan Keselamatan tentang Pacaran dan Pernikahan Beda Agama - Budiatmaja, Rudy; Djojosuroto, Kinayati (Divinitas Jurnal Filsafat dan Teologi Kontekstual, 2024)
Many teenagers say that love can be blind and that love can be carried out by men and women of different religions because of the wrong understanding which states that it is just a momentary pleasure and only satisfies a man's lust without following the current rules or norms of decency. The aim of the current research is to prioritize Soteriology as a spiritual provision for teenagers to face changes in their attitudes and face the wider social circle of all teenagers who are entering the transition period from childhood to adulthood, which includes all growth and development in relationships because of this the church and family are present. to teach the truth about the realities of life. Qualitative literature study methods are used to obtain accurate data related to this scientific work, the sources are the Bible, books and other articles related to the title discussed. The research results show the doctrine of soteriology and the role of the church as a teaching "agent" in teaching the Word of God because Soterology is the certainty of salvation in the Lord Jesus and is the basis for Christian teenagers to face changes in growth and development including dating up to marriage and refusing to date up to interfaith marriages . The conclusion of this research states that the church and family play a full role in being responsible for the future of teenagers so that they do not choose the wrong boyfriend or girlfriend as their lifelong companion and the church and family advise against choosing a boyfriend who has a different belief, let alone until marriage.AbstrakBanyak kalangan remaja mengatakan cinta itu bisa buta dikarenakan adanya pemahaman yang keliru yang menyebutkan bahwa hanya sekedar nikmat sesaat dan hanya memuaskan hawa nafsu seorang laki-laki tanpa mengikuti aturan atau norma kesusilaan yang berlaku saat ini. Tujuan riset saat ini mengutamakan Soteriologi sebagai pembekalan secara rohani kepada remaja untuk menghadapi perubahan sikapnya dan menghadapi pergaulan yang semakin luas kepada semua remaja yang memasuki masa peralihan dari masa anak ke masa dewasa, yang meliputi semua pertumbuhan dan perkembangan dalam pergaulan karena itu gereja dan keluarga hadir untuk mengajarkan tentang kebenaran atas kenyataan hidup. Metode kualitatif studi pustaka digunakan untuk memperoleh data yang akurat berhubungan dengan karya ilmiah ini, sumbernya dari Alkitab, buku-buku dan artikel artikel lainnya yang sehubungan dengan judul yang dibahas. Hasil riset menunjukkan doktrin soteriologi dan peran gereja sebagai “agen” pengajar dalam mengajarkan Firman Tuhan sebab Soterologi sebagai kepastian keselamatan dalam Tuhan Yesus dan menjadi dasar bagi anak remaja Kristen menghadapi perubahan pertumbuhan dan perkembangan termasuk berpacaran sampai pada pernikahan. Simpulan riset ini menyatakan Gereja dan keluarga berperan penuh atas tanggung jawab masa depan para remaja agar tidak salah memilih pacar sebagai pendamping hidupya seumur hidup dan pihak gereja dan keluarga menyarankan agar tidak memilih pacar yang berbeda keyakinan apalagi sampai pernikahan.